Implementing Active Learning Strategies in Teaching Building Systems, Safety, and Services: A Case Study in Civil Engineering Education - Rangwala, Husain; Kalaria, Jay; Thoriya, Amit (Journal of Engineering Education Transformations, 2026)
Active learning has proven to be a successful strategy to enhance engagement and applied competence amongst learners of engineering. Traditional lecture-based courses included in civil engineering education tend to lack the linkage between theoretical and field-based applications. This paper provides a case study of the implementation of project-based and experiential learning environments and the course Building Systems, Safety, and Services (BSSS) in order to increase student engagement and applied learning. Activities that are incorporated in the methodology include plumbing and electrical layout drafting, poster and PowerPoint presentation, and fire-safety demonstration that is facilitated by instructors and professional expert sessions. The descriptive statistics and qualitative reflections were used to analyze the student feedback of 28 participants. The findings have shown that there is a great deal of improvement in visualization, design, and safety awareness with more than 90 percent of students stating that they have increased confidence and practical learning outcomes. The results are also consistent with other literature that identifies the usefulness of interactive pedagogies in engineering education. The study concludes that active-learning frameworks not only fill the gap between theory and practice but also resonate with Sustainable Development Goals (SDG 4 and SDG 11), which make civil engineers employable and prepare them to meet industry challenges.